Pengaruh Konsentrasi dan Frekuensi MOL Bonggol Pisang terhadap Pertumbuhan dan Hasil Tanaman Buncis (Phaseolus vulgaris, L.) di Musim Hujan - Antonius Dedi Bere (Savana Cendana, 2022)
This research aims to; (i) Determine the correct MOL concentration of banana weevil on the growth and yield of beans in the rainy season; (ii) Determine the correct MOL frequency of banana weevil for growth and yield of beans in the rainy season. This research will be carried out within 3 months from april-june 2020, at km 09, Kecurah Kota, North Central Timor Regency using the experimental method in the field with a factorial randomized block design (RBD). Factor 1 Concentration of MOL banana weevil (K) consisting of 3 levels: Control (K0), 1 liter: 4 liters of water (K1), 1 liter: 5 liters of water, (K2). The second factor is the frequency of watering (F), which consists of 3 levels: 1 week (F1), 2 weeks (F2), 3 weeks (F3). These two factors were combined so that 9 treatment combinations were obtained with 3 replications, 27 treatments were obtained. With the following combination: K0F1, K0F2, D0F3, K1F1, K1F2, K1F3, K2F1, K2F2, K2F3. The results showed that the best MOL concentration of banana weevil for growth and yield of beans in the rainy season was a concentration of 1: 5L and the best MOL weevil frequency for growth and yield of beans in the rainy season was 2 weeks and 3 weeks.